Electromyography-based analysis of human upper limbs during 45-day head-down bed-rest. (March 2016) - Fu, Anshuang; Wang, Chunhui; Qi, Hongzhi; Li, Fan; Wang, Zheng; He, Feng; Zhou, Peng; Chen, Shanguang; Ming, Dong
Abstract: Muscle deconditioning occurs in response to simulated or actual microgravity. In spaceflight, astronauts become monkey-like for mainly using their upper limbs to control the operating system and to complete corresponding tasks. The changes of upper limbs׳ athletic ability will directly affect astronauts' working performance. This study investigated the variation trend of surface electromyography (sEMG) during prolonged simulated microgravity. Eight healthy males participating in this study performed strict 45-day head-down bed-rest (HDBR). On the 5th day of pre-HDBR, and the 15th, the 30th and the 45th days of HDBR, the subjects performed maximum pushing task and maximum pulling task, and sEMG was collected from upper limbs synchronously. Each subject's maximum volunteer contractions of both the tasks during these days were compared, showing no significant change. However, changes were detected by sEMG-based analysis. It was found that integrated EMG, root mean square, mean frequency, fuzzy entropy of deltoid, and fuzzy entropy of triceps brachii changed significantly when comparing pre-HDBR with HDBR. The variation trend showed a recovery tendency after significant decline, which is inconsistent with the monotonic variation of lower limbs that was proved by previous research. These findings suggest that EMG changes in upper limbs during prolonged simulated microgravity, but has different variation trend from lower limbs. Highlights: IEMG, RMS, MNF, FuzzyEn are sensitive to test the upper limb's sEMG changing. Significant change was found in sEMG parameters, but not in MVC of upper limbs. TB, DT and BR were the three main muscles showing significant changes. sEMG parameters showed non-monotonic decreases. Comparing with minimum value, a recovery rise of HDBR45 was detected.